Utilization and effects of mobile electronic clinical decision support on pediatric asthma care quality in the emergency department and inpatient setting. Issue 2 (19th April 2021) - Kerns, Ellen; McCulloh, Russell; Fouquet, Sarah; McDaniel, Corrie; Ken, Lynda; Liu, Peony; Kaiser, Sunitha
Abstract: Objective: To determine utilization and impacts of a mobile electronic clinical decision support (mECDS) on pediatric asthma care quality in emergency department and inpatient settings. Methods: We conducted an observational study of a mECDS tool that was deployed as part of a multi-dimensional, national quality improvement (QI) project focused on pediatric asthma. We quantified mECDS utilization using cumulative screen views over the study period in the city in which each participating site was located. We determined associations between mECDS utilization and pediatric asthma quality metrics using mixed-effect logistic regression models (adjusted for time, site characteristics, site-level QI project engagement, and patient characteristics). Results: The tool was offered to clinicians at 75 sites and used on 286 devices; cumulative screen views were 4191. Children's hospitals and sites with greater QI project engagement had higher cumulative mECDS utilization. Cumulative mECDS utilization was associated with significantly reduced odds of hospital admission (OR: 0.95, 95% CI: 0.92–0.98) and higher odds of caregiver referral to smoking cessation resources (OR: 1.08, 95% CI: 1.01–1.16). Discussion: We linked mECDS utilization to clinical outcomes using a national sample and controlling for important confounders (secular trends, patient case mix, and concomitant QI efforts). We found mECDS utilization was associated with improvements in multiple measures of pediatric asthma care quality. Conclusion: mECDS has the potential to overcome barriers to dissemination and improve care on a broad scale. Important areas of future work include improving mECDS uptake/utilization, linking clinicians' mECDS usage to clinical practice, and studying mECDS's impacts on other common pediatric conditions.